PENGEMBANGAN SISTEM AUTOREPLY BERKONSEP MODEM AUTO-SELECTION PADA QUICK COUNT PILKADA VIA SMS - Dwi Sakethi; Ossy Dwi Endah Wulandari; Serlina Muhar (Jurnal Komputasi, 2015)
SMS gateway is a service Â receive massages from the outside and can send counterpunch automatically into a number of purposes. SMS gateway it has been much used so one example in research is SMS a gateway to the quick count pilkada. In this research autoreply feature is added to sending SMS. Autoreply is add modem concept that send SMS from 3 modems, the modems contain 3 card that used different operator. So every system that received inbox will be replied automatically from modem that help the sending and receiving data using operator cellular service that same with operator cellular sent. Autoreply feature added to ensure and accelerate the acquisition of information does reach the sound at the time of performance of the elections and 3 modem used to reduce toll rates because the system reply SMS in accordance with the service provider used by the sender.